Strange way of life [videorecording (DVD)] - Almodóvar, Pedro; Pascal, Pedro; Hawke, Ethan, 1970- (Sony Pictures Home Entertainment, 2024)
A short film by director Pedro Almodovar. After twenty-five years, Silva rides a horse across the desert to visit his ex-lover, now friend, Sheriff Jake. A lifetime after their shared stint as hired gunmen, they celebrate their reunion. However, the next morning, it is revealed the trip is not to revel in the memory of their friendship.